COVID-19: An ayurvedic appraisal - Darshna H Pandya (Wolters Kluwer Medknow Publications, 2020)
Introduction: The novel coronavirus disease (COVID-19) has been identified as the cause of an outbreak of respiratory illness, transmitted by breathing of or contact with infected droplets and the clinical features characterized by a variable degree of severity of symptoms, ranging from a mild upper respiratory tract illness to severe interstitial pneumonia and acute respiratory distress syndrome. As of mid of August 2020, this has been spread to 218 countries with more than two billion confirmed cases, including near about 7.5 lakh deaths. Objectives: The aim was to understand the disease COVID-19 in Ayurvedic phraseology. Material and Data Source: To fulfill the aim, Ayurvedic classical literature starts from Brihatrayee to Siddhanta Nidana (by Gananath Sen) has been referred and published literature available on COVID-19 was searched out from PubMed search. Results: No one to one match of the disease found in Ayurveda, but on the basis of scattered references regarding Jwara and Janapadodhvamsa, an attempt has been made to understand COVID-19 in Ayurvedic phrasing. Conclusion: The disease COVID-19 may be categorized as Vayu-Kapha predominant Sannipataja Agantuja type of Jwara.